IDEOLOGICAL DETERMINATION OF SOCIAL TRANSFORMATIONS IN MODERN SOCIETY - Nikolaevich Ravochkin, Nikita; Viktorovich Lunev, Vladimir; Alexandrovna Korol, Natalia; Anatolyevna Luneva, Tatyana; Lospanovna Mongush, Alla; Vladimirovich Rakhinskiy, Dmitriy (Revista Inclusiones, 2020)
The article deals with the specific nature of the ideological determination of social transformations at the current stage of global development. Ideas are defined as bases for the implementation of social changes. A connection is established between ideas, social imaginary and geographic localization of intellectual networks. Options for implementing social transformations are presented. The main options include modernization, revolution and coup. It is proved that the efficiency of performing regulative functions in society directly depends on the authorities and intellectuals' awareness of the state of the public life spheres within absolutely any state. The characteristic features of the mechanism of ideological determination are revealed. The process of the generation of ideas in the intellectual network is shown.